54 Punch Designs (Hair Transplantation, 2023)
Circular round punches have been used for harvesting grafts with both the punch grafting technique described in the early literature by Okuda and Orentriech and the contemporary follicular unit excision (FUE) techniques of today. They varied greatly with respect to size, cutting-edge sharpness, and design. For far too long punches were manufactured with little documentation about their specific design. In addition, very often, manufactures did not use high-grade materials now available that extend the life of FUE punches. In 2013, a committee formed by the International Society of Hair Restoration Surgery (ISHRS) to standardize the language used in FUE published its findings on various FUE devices, terminology, and punch designs and shapes. FUE punches were described and categorized by various characteristics including the specific diameters, the location of cutting edge, the punch size determined by to the diameter of its cutting edge, and whether the cutting edge was sharp or blunt. Recently, a variety of new punch designs and systems were introduced to the FUE community that broaden the hair restoration surgeon’s options when selecting punches for FUE harvesting. Because of the newer punch designs, the ISHRS and FUE community will need to expand or revise to some degree the current categories of FUE punches. Some of the newer punch designs and systems will be described in this chapter and in Chapter 67.
Keywords: sharp punch; blunt punch; trumpet punch; open punch; flared punch; Hex punch; DrUPunch Curl Punch; hybrid punch